First Evaluation of Microplastic Content in Benthic Filter-feeders of the Gulf of La Spezia (Ligurian Sea) - Guido Bonello; Paolo Varrella; Luigi Pane (Journal of Aquatic Food Product Technology, 2018)
The ingestion and retention of microplastics of filter-feeder organisms represent a risk for the final consumers and the environment. Biomonitoring is necessary to deal with the effects of plastic material pollution. The selection of the monitored organisms strongly affects the relevance of the results and the understanding of the environmental conditions. The results discussed in this paper highlight the differences in the estimate of microplastic pollution depending on the species subject of study. Ascidia spp. specimens retained a value five-fold higher (0.62 MP/g) than bivalve species (Crassostrea gigas 0.11 MP/g; Mytilus galloprovincialis 0.05 MP/g; Anomia ephippium 0.12 MP/g).